HOLOGRAPHY– THE FASCINATING WORLD OF 3-D VIEWING (SCHOOL SCIENCE, 2010)
Memories of people, events etc. are better stored in the form of photographs. In fact, the technology of photography has been with us for a long time. Regular photograph “freezes” a two dimensional image of the three-dimensional world, thereby enabling only a two-dimensional view of reality. Standard photographic film registers the total light intensity (which is square of amplitude of light wave) falling on each point of the film during exposure i.e. when the shutter is open. The resulting image is a two-dimensional mapping which contains only the intensity attributes of the wave. The phase attributes of the wave related to the depth of the field are therefore lost. An ordinary photography, therefore, loses the phase completely. It records only the intensities. However, if both the intensity and the phase attributes of the wave are recorded, one can get a three-dimensional image of the object. This is achieved by using the principles of what is known as holography.